Differentially expressed proteins in human breast cancer cells sensitive and resistant to paclitaxel - Pavlikova, Nela; Bartonova, Irena; Dincakova, Lucia; Halada, Petr; Kovar, Jan (International journal of oncology, 2014)
The resistance of cancer cells to chemotherapeutic drugs represents a major problem in cancer treatment. Despite all efforts, mechanisms of resistance have not yet been elucidated. To reveal proteins that could be involved in resistance to taxanes, we compared protein expression in whole cell lysates of SK-BR-3 breast cancer cells sensitive to paclitaxel and in lysates of the same line with acquired resistance to paclitaxel. The resistant SK-BR-3 cell line was established in our lab. Protein separation was achieved using high-resolution 2D-electrophoresis, computer analysis and mass spectro-metry. With these techniques we identified four proteins with different expression in resistant SK-BR-3 cells, i.e., serpin B3, serpin B4, heat shock protein 27 (all three upregulated) and cytokeratin 18 (downregulated). Observed changes were confirmed using western blot analysis. This study suggests new directions worthy of further study in the effort to reveal the mechanism of resistance to paclitaxel in breast cancer cells.
Keywords: Serpins; Adenocarcinoma; 2D gelová elektroforéza; Antineoplastic Agents, Phytogenic; Humans; fytogenní protinádorové látky; Proteomics; serpiny; Female; Blotting, Western; lidé; chemorezistence; Antigens, Neoplasm; proteomika; antigeny nádorové; Breast Neoplasms; ženské pohlaví; spektrometrie hmotnostní - ionizace laserem za účasti matrice; paclitaxel; Electrophoresis, Gel, Two-Dimensional; nádorové buněčné linie; nádory prsu; keratin-18; HSP27 Heat-Shock Proteins; adenokarcinom; proteiny tepelného šoku HSP27; Cell Line, Tumor; Paclitaxel; western blotting; Spectrometry, Mass, Matrix-Assisted Laser Desorption-Ionization; Drug Resistance, Neoplasm; Keratin-18